Find the path for mobile Robot using RRT and PSO technique - Tong , Thành Trung; Ngo , Văn Thuyên (Journal of Technical Education Science, 2021)
RRT (Rapidly-exploring Random Tree) is a random data structure, designed for efficient search in the multi-dimensional space. RRT can be regarded as a technique to create random points in nonlinear systems, especially suited for problems of path planning for mobile robot with nonholonomic and kinodynamic constraints. Particle Swarm Optimization is an efficient algorithm for optimization problems. This paper presents the application of RRT combining with PSO algorithm to find a path for mobile robots in a known environment. PSO is used to search for the optimal angular and linear velocities so that the robot can move from one position to the next one on the tree. Simulation results in Matlab show that the proposed method is efficient for finding the path for mobile robot in a known environment.